Time‐stepping finite element analysis on the influence of rotational flux on local core losses of AC electrical machines. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of the paper is to study the influence of rotational flux on local core losses of the motors, which is difficult to distinguish the iron losses caused by rotational flux in certain electric machines through experiment. Therefore, time‐stepping finite element method (T‐S FEM) is used to consider the rotational flux and to predict the local core losses.Design/methodology/approach – Time‐stepping finite element method.Findings – It is found that, in stator side, rotational flux mainly exists in tooth root and yoke area near the bottom of stator slot, those area is about 45 percent of total stator core area; in rotor side, due to slot harmonic field, the rotational flux mainly exists in the tip of tooth.Originality/value – Through analyzing the magnetization characteristics at different positions in stator and rotor cores by T‐S FEM, the influence of rotational flux on local core losses of AC electric machines is studied. Acknowledgements : This work is supported in part by the National Natural Science Foundation of China (51307050) and Fundamental Research Funds for the Central Universities.